Research Note: Evaluating fecal shedding of oocysts in relation to body weight gain and lesion scores during Eimeria infection - K.M. Chasser (Poultry Science, 2020)
Coccidiosis has been a pervasive disease within the poultry industry, with test parameters used to measure effectiveness of treatment strategies often being subjective or influenced by non–disease-related activity. Four experiments were completed, which examined several test parameters of coccidiosis, including body weight gain (BWG), lesion scores, and oocysts per gram of feces (OPG). Each experiment included at least 2 parameters for measuring coccidial infection in chickens and turkeys. In experiment 1, an inoculated control was measured against 3 anticoccidial groups, whereas in experiments 2 to 4, noninoculated and inoculated controls were compared via BWG and OPG. Lesion scores were also included in experiments 1, 3, and 4. Experiment 4 resulted in high correlation, via Pearson correlation coefficient, between BWG and OPG (r = −0.69), very high correlation between OPG and lesion score (r = 0.86), and moderate correlation between BWG and lesion score (r = −0.49). Lesion scores proved to be effective in confirming Eimeria infection, although they did not correlate well with BWG or OPG. Each parameter tended to provide more useful information when lined up with the Eimeria life cycle. Incorporation of OPG, with BWG and lesion scores, as test parameters to measure coccidiosis intervention strategies, provides a global description of disease that may not otherwise be observed with the 2 latter measurements alone.